O futebol como vivência de lazer de estudantes do ensino médio em cidades pequenas do interior de Minas Gerais - Mateus Alexandre Silva (2019)
The present study aims to analyze football as one of the main leisure experiences in the routine of high school students in six countryside cities of Minas Gerais, with less than five thousand inhabitants. It is tries to know the experiences practiced and enjoyed with football and its dedicated time as leisure, to analyze the access conditions to football experiences, as well as to understand the establishment of the relationship of these students while football supporters. As a method, a structured questionnaire was applied to students from six state schools in the center-west of Minas Gerais, in the second half of 2018. The collected data were treated using the Statistical Package for Social Sciences (SPSS), compared to the selected bibliography and interpreted according to the division into 4 football related categories of analysis: playing; supporting; watching on TV; and playing virtual games. In the obtained results, football was present as one of the main leisure experiences of the youngsters, but there was an unfavorable disparity between female respondents in terms of the occupation of real and virtual spaces. Football supporters, in turn, appears in equal proportion for both, male and female, revealing itself far from the stadiums, being TV, the main link between the team and its supporters. At last, public spaces, more specifically fields, courts and schools, often appear as the main scenarios for football practice. As per playing virtual football games, the use of personal equipment, in the domestic environment, stands out.